Consumer perception of Nellore and crossbred cattle beef: flavor as the main driver of acceptance across wet-aging periods - Amanda Gobeti Barro; Guilherme Agostinis Ferreira; Daniela Kaizer Terto; Natalia Nami Ogawa; Sandra Maria Simonelli; Gregori Rovadoscki; Marcelo Coutinho; Ana Maria Bridi (International Journal of Gastronomy and Food Science, 2026)

Climate change and conservation of threatened tree species in the Doce River Basin: an ecological niche modeling approach - Cecília Loren-Silva; Rodrigo Gomes Gorsani; Alex Josélio Pires Coelho; Carlos Mário Galván-Cisneros; Rafaela Brandão-Gomes; Renato Augusto Ferreira de Lima; Carlos Moreira Miquelino Eleto Torres; Nathália Silva; Marcelo Simonelli; Markus Gastauer; Fabiana Bonani; João Augusto Alves Meira-Neto (Biodiversity and Conservation, 2026)
Tropical forests, particularly the Atlantic Forest, are among the most biodiverse and threatened ecosystems on Earth. Intense fragmentation, historical deforestation, and climate change have compromised their integrity and endangered endemic and rare species. The situation is even more critical in the Doce River Basin (DRB), a biodiversity hotspot in southeastern Brazil, due to the expansion of pastureland and mining, as well as the 2015 Mariana disaster. Understanding how future climate may affect the persistence of threatened tree species in the region is essential. This study evaluated the effects of climate scenarios on the distribution of 26 rare and/or threatened tree species in the DRB. We used Species Distribution Models (SDMs), combining algorithms (GLM, RDF, SVM, MaxEnt) into a consensus ensemble model under SSP3-7.0 and SSP5-8.5 scenarios for 2050 and 2090. Climatic, topographic, and edaphic variables were predictors, with climate explaining most environmental variation. Among the 26 species, 19 are projected to lose over 75% of their suitable area, with local extinction likely for range-restricted and specialized species such as Handroanthus arianeae and Grazielodendron rio-docensis . Species associated with mature forests and humid microclimates were most severely affected, while some generalists showed resilience, maintaining or expanding suitable areas. Although all species retain some suitable habitats within Protected Areas (PAs), results indicate the current PA network will be insufficient for long-term conservation. Complementary strategies such as assisted translocation, habitat connectivity, and priority-area identification based on climate projections are needed. This study provides critical insights for policies and land-use planning aimed at conserving the DRB’s threatened flora.

Phylogenetic diversity recovery along Atlantic Forest succession: The potential for conserving evolutionary history - Alex Josélio Pires Coelho; Carlos Mário Galván-Cisneros; Pedro Manuel Villa; Heitor Mancini Teixeira; Fabio Antônio Ribeiro Matos; Alice Cristina Rodrigues; Nayara Mesquita Mota; Fernando da Costa Britod Lacerda; Fábia Maria dos Santos Souza; Nathália Vieira Hissa Safar; Nathália Silva; Fabiana Bonani; et al. (Biological Conservation, 2026)

Resistance without trade-offs: wood density drives survival while potential size constrains early growth in tropical forest restoration - Jeanpierre Rodríguez-Mirano; Marcelo Simonelli; Luiz Fernando Silva Magnago (Plant Ecology, 2026)
High seedling mortality is a key bottleneck in tropical forest restoration, but the mechanisms governing the survival–growth trade-off remain unclear. We evaluated seedling performance in a high-diversity restoration planting in Goytacazes National Forest (Tableland Atlantic Forest), monitoring 771 individuals from 54 native species over three years (2012–2015). Using Stratified Cox Proportional Hazards models for survival and Linear Mixed Models for relative growth rates (RGR), we also quantified spatial variance (ICC). Wood Density (WD) was the strongest predictor of survival: high-WD species had lower mortality risk (HR = 0.82), independent of spatial heterogeneity. The study period included a flood (2013) and a drought (2015), and this context—together with the very low herbivory—suggests that extreme climatic events drove the survival advantage of high-WD species. Contrary to expectations from the Plant Economics Spectrum, high WD did not reduce vertical or radial growth. Furthermore, we found a non-significant negative trend ( p = 0.146) between potential maximum height (H max ​) and early growth, indicating that initial performance was independent of the species’ eventual vertical niche. Our results suggest that high-WD species show higher survival without early-growth costs, highlighting their strategic value for restoration in high-stress environments.

LandFrag : A Dataset to Investigate the Effects of Forest Loss and Fragmentation on Biodiversity - Thiago Gonçalves‐Souza; Maurício Humberto Vancine; Nathan J. Sanders; Nick M. Haddad; Lucas Cortinhas; Anne Lene T. O. Aase; Willian Moura de Aguiar; Marcelo Adrian Aizen; Víctor Arroyo‐Rodríguez; Arturo Baz; Maíra Benchimol; Enrico Bernard; et al. (Global Ecology and Biogeography, 2025)
Motivation The accelerated and widespread conversion of once continuous ecosystems into fragmented landscapes has driven ecological research to understand the response of biodiversity to local (fragment size) and landscape (forest cover and fragmentation) changes. This information has important theoretical and applied implications, but is still far from complete. We compiled the most comprehensive and updated database to investigate how these local and landscape changes determine species composition, abundance and trait diversity of multiple taxonomic groups in forest fragments across the globe. Main Types of Variables Contained We gathered data for 1472 forest fragments, providing information on the abundance and composition of 9154 species belonging to vertebrates, invertebrates, and plants. For 2703 of these species, we obtained more than 20 functional traits. We provided the spatial location and size of each fragment and metrics of landscape composition and configuration. Spatial Location and Grain The dataset includes 1472 forest fragments sampled in 121 studies from all continents except Antarctica. Most datasets (77%) are from tropical regions, 17% are from temperate regions, and 6% are from subtropical regions. Species abundance and composition were collected at the plot or fragment scale, whereas the landscape metrics were extracted with buffer size ranging from a radius of 200–2000 m. Time Period and Grain Data on the abundance of species and community composition were collected between 1994 and 2022, and the landscape metrics were extracted from the same year that a given study collected the abundance and composition data. Major Taxa and Level of Measurement The studied organisms included invertebrates (Arachnida, Insecta and Gastropoda; 41% of the datasets), vertebrates (Amphibia, Squamata, Aves and Mammalia; 44%), and vascular plants (19%), and the lowest level of identification was species or morphospecies. Software Format The dataset and code can be downloaded on Zenodo or GitHub.

Secondary forest fragments offer important carbon and biodiversity cobenefits - Fabio A. R. Matos; Luiz F. S. Magnago; Carlos Aquila Chan Miranda; Luis F. T. de Menezes; Markus Gastauer; Nathália V. H. Safar; Carlos E. G. R. Schaefer; Mônica P. da Silva; Marcelo Simonelli; Felicity A. Edwards; Sebastião V. Martins; João A. A. Meira‐Neto; et al. (Global Change Biology, 2020)
Tropical forests store large amounts of carbon and high biodiversity, but are being degraded at alarming rates. The emerging global Forest and Landscape Restoration (FLR) agenda seeks to limit global climate change by removing carbon dioxide from the atmosphere through the growth of trees. In doing so, it may also protect biodiversity as a free cobenefit, which is vital given the massive shortfall in funding for biodiversity conservation. We investigated whether natural forest regeneration on abandoned pastureland offers such cobenefits, focusing for the first time on the recovery of taxonomic diversity (TD), phylogenetic diversity (PD) and functional diversity (FD) of trees, including the recovery of threatened and endemic species richness, within isolated secondary forest (SF) fragments. We focused on the globally threatened Brazilian Atlantic Forest, where commitments have been made to restore 1 million hectares under FLR. Three decades after land abandonment, regenerating forests had recovered ~20% (72 Mg/ha) of the above‐ground carbon stocks of a primary forest (PF), with cattle pasture containing just 3% of stocks relative to PFs. Over this period, SF recovered ~76% of TD, 84% of PD and 96% of FD found within PFs. In addition, SFs had on average recovered 65% of threatened and ~30% of endemic species richness of primary Atlantic forest. Finally, we find positive relationships between carbon stock and tree diversity recovery. Our results emphasize that SF fragments offer cobenefits under FLR and other carbon‐based payments for ecosystem service schemes (e.g. carbon enhancements under REDD+). They also indicate that even isolated patches of SF could help to mitigate climate change and the biodiversity extinction crisis by recovering species of high conservation concern and improving landscape connectivity.

Would protecting tropical forest fragments provide carbon and biodiversity cobenefits under REDD +? - Luiz Fernando S. Magnago; Ainhoa Magrach; William F. Laurance; Sebastião V. Martins; João Augusto A. Meira‐Neto; Marcelo Simonelli; David P. Edwards (Global Change Biology, 2015)
Tropical forests store vast amounts of carbon and are the most biodiverse terrestrial habitats, yet they are being converted and degraded at alarming rates. Given global shortfalls in the budgets required to prevent carbon and biodiversity loss, we need to seek solutions that simultaneously address both issues. Of particular interest are carbon‐based payments under the Reducing Emissions from Deforestation and Forest Degradation ( REDD +) mechanism to also conserve biodiversity at no additional cost. One potential is for REDD + to protect forest fragments, especially within biomes where contiguous forest cover has diminished dramatically, but we require empirical tests of the strength of any carbon and biodiversity cobenefits in such fragmented systems. Using the globally threatened Atlantic Forest landscape, we measured above‐ground carbon stocks within forest fragments spanning 13 to 23 442 ha in area and with different degrees of isolation. We related these stocks to tree community structure and to the richness and abundance of endemic and IUCN Red‐listed species. We found that increasing fragment size has a positive relationship with above‐ground carbon stock and with abundance of IUCN Red‐listed species and tree community structure. We also found negative relationships between distance from large forest block and tree community structure, endemic species richness and abundance, and IUCN Red‐listed species abundance. These resulted in positive congruence between carbon stocks and Red‐listed species, and the abundance and richness of endemic species, demonstrating vital cobenefits. As such, protecting forest fragments in hotspots of biodiversity, particularly larger fragments and those closest to sources, offers important carbon and biodiversity cobenefits. More generally, our results suggest that macroscale models of cobenefits under REDD + have likely overlooked key benefits at small scales, indicating the necessity to apply models that include finer‐grained assessments in fragmented landscapes rather than using averaged coarse‐grained cells.